A06 Chdi-00340246, A Kynurenine Monooxygenase Inhibitor As Potential Therapeutic Agent For The Treatment Of Huntington's Disease. (17th September 2014) - Toledo-Sherman, L; Prime, ME; Mitchell, W; Brown, C; Gaines, S; Johnson, PD; Mitchell, W; Pena, P; Reed, L; Sehmi, S; Selvaratnam, S; Winkler, D; et al.
Abstract : Deregulation of the Kynurenine Pathway, has been causally implicated in the pathophysiology of HD. Metabolites of this pathway have been shown to be neurotoxic (3-Hydroxy kynurenine (3-HK) and Quinolinic Acid (QA), while kynurenine (KYN) and kynurenic acid (KYNA) have been described as neuroprotective. Pathway deregulation showing increased in the neurotoxic metabolites has been reported in postmortem striatum and cortex samples of early grade HD brains as compared to controls, and in HD mice models R6/2, YAC128 and HdhQ111. The collective evidence for the implication of these metabolites in the pathophysiology of HD highlights the KP pathway as an attractive therapeutic intervention point in this disease. Inhibition of KMO, a key enzyme in the pathway, should shunt the pathway away from the toxic metabolites 3-HK and QA and towards the formation of the protective metabolite KYNA. The potential of KMO as HD target has been shown in a yeast, flies and mice models of HD. This talk will describe CHDI's efforts towards obtaining a series of potent and selective inhibitors of KMO. Will speak to the PK/PD effects that we have obtained with our lead compound CHDI-00340246 ('246), a compound that warrants further consideration for pharmaceutical development in HD. '246 has been declared a clinical candidate and an upcoming GLP-tox study in rodents and NHPs is planned. In addition we will present the methods development efforts that have been undertaken in support of a clinical biomarker study.